Recovery of activities of daily living in COVID-19 patients requiring intensive care unit or medical care unit: an observational study on the role of rehabilitation in the subacute phase - Notarstefano, Chiara; Bertolucci, Federica; Miccoli, Mario; Posteraro, Federico (Frontiers in Rehabilitation Sciences, 2023)
To describe functional status of a cohort of subacute COVID-19 patients treated in a dedicated Rehabilitation Unit and to compare functional outcomes between patients previously hospitalized in Intensive Care Unit (ICU-group) and patients assisted in Medical Care Unit (MCUgroup). Materials and Methods: Clinical and functional evaluations were performed at admission and discharge. Functional status was assessed using Barthel Index (BI), Functional Ambulation Categories (FAC), Trunk Control Test (TCT) and Dysphagia Outcome and Severity Score (DOSS). All patients received multidisciplinary tailored rehabilitation. Results: We evaluated 171 patients (mean age 67,7±11,9; 117 male), 110 coming from ICU (mean age 63,24±10,9), 61 coming from MCU (mean age 75,75±9,09). ICU-group showed worse functional status at admission compared to MCU-group (BI 2,5 (0,20) vs 20 (10,60), FAC 0 (0,0) vs 0 (0,2), TCT 61 (42, 100) vs 100 (61,100), DOSS 5(1,7) vs 7(7,7)) and had significantly longer hospital stay. At discharge all functional scales were improved with no statistically significant differences between groups. Conclusions: Early rehabilitation of COVID-19 survivors improves functional recovery closing the initial gap between ICU and MCU groups. And it is effective to improve functional outcome reducing the costs for longer term assistance of COVID-19 patients.